Validity Analysis of the Development of Integrated Global Warming Digital Teaching Material using Ethno-PBL to Improve Students Critical Thinking Ability - Fajri, Muhamad Fajri; Asrizal, Asrizal; Amir, Harman; Yumna, Hayyu (Universitas Negeri Padang, 2025)
Critical thinking is a key competency required in 21st-century learning; however, field observations indicate that students’ critical thinking skills remain relatively low. This condition is closely related to the use of teaching materials that have not optimally implemented the Problem Based Learning (PBL) model and have not integrated local cultural contexts. To address this gap, this study developed digital teaching materials on global warming integrated with Ethno-Problem Based Learning (Ethno-PBL). The purpose of this study was to determine the validity of the developed Ethno-PBL-based digital teaching materials as a foundation for supporting the development of students’ critical thinking skills. This research employed a research and development approach, limited to the product validation stage conducted by expert validators. The validation process evaluated five aspects: material substance, learning design, visual communication, software utilization, and Ethno-PBL integration. The results showed that the developed digital teaching materials achieved a high level of validity, with an average validity score of 0.94. Specifically, the validity scores for material substance, learning design, visual communication, software utilization, and Ethno-PBL integration were 0.90, 0.95, 0.96, 0.97, and 0.94, respectively. These findings indicate that the Ethno-PBL-based digital teaching materials are valid, feasible, and beneficial for use in physics learning on global warming topics, and have the potential to facilitate more contextual, meaningful, and critical learning experiences for students.